Neutralizing properties of LY315920 toward snake venom group I and II myotoxic phospholipases A2 - Bryan Quirós, Wendy (2019)
A need exists to develop specific and clinically useful inhibitors of toxic enzymes present in snake venoms, responsible for severe tissue damage and life-threatening effects occurring in thousands of people suffering envenomations globally. LY315920 (Varespladib, S-5920, A-001), a low molecular weight drug developed to inhibit several human secreted phospholipases A2 (PLA2s), was recently shown to also inhibit PLA2s in whole snake venoms with high potency, yet no studies have examined its direct effect on purified snake venom PLA2s. This work evaluated the ability of LY315920 to neutralize the enzymatic and toxic activities of three isolated PLA2 toxins of structural groups I (pseudexin) and II (crotoxin B and myotoxin I), and their corresponding whole venoms. In vitro, LY315920 inhibited the catalytic activity of these three enzymes upon a synthetic substrate. The drug also blocked their cytotoxic effect on cultured murine myotubes. In mice, preincubation of the toxins or venoms with LY315920, followed by their intramuscular injection, resulted in significant inhibition of muscle damage. Finally, immediate, independent injection of LY315920 at the site of toxin or venom inoculation also resulted in a large reduction of myonecrosis in the case of pseudexin and myotoxin-I, and of Pseudechis colletti and Bothrops asper whole venoms, suggesting a possible method of drug delivery in emergency situations. Present findings add evidence to suggest the possibility of using LY315920 as a field antidote in snakebites, aiming to limit the myonecrosis induced by many venom PLA2s in the clinical setting.